Broad Ultrastructural and Transcriptomic Changes Underlie the Multinucleated Giant Hemocyte Mediated Innate Immune Response against Parasitoids - Gyöngyi Cinege; Lilla B. Magyar; Attila L. Kovács; Zita Lerner; Gábor Juhász; David Lukacsovich; Jochen Winterer; Tamás Lukacsovich; Zoltán Hegedűs; Éva Kurucz; Dan Hultmark; Csaba Földy; et al. (Karger Publishers, 2021)
Multinucleated giant hemocytes (MGHs) represent a novel type of blood cell in insects that participate in a highly efficient immune response against parasitoid wasps involving isolation and killing of the parasite. Previously, we showed that circulating MGHs have high motility and the interaction with the parasitoid rapidly triggers encapsulation. However, structural and molecular mechanisms behind these processes remained elusive. Here, we used detailed ultrastructural analysis and live cell imaging of MGHs to study encapsulation in Drosophila ananassae after parasitoid wasp infection. We found dynamic structural changes, mainly driven by the formation of diverse vesicular systems and newly developed complex intracytoplasmic membrane structures, and abundant generation of giant cell exosomes in MGHs. In addition, we used RNA sequencing to study the transcriptomic profile of MGHs and activated plasmatocytes 72 h after infection, as well as the uninduced blood cells. This revealed that differentiation of MGHs was accompanied by broad changes in gene expression. Consistent with the observed structural changes, transcripts related to vesicular function, cytoskeletal organization, and adhesion were enriched in MGHs. In addition, several orphan genes encoding for hemolysin-like proteins, pore-forming toxins of prokaryotic origin, were expressed at high level, which may be important for parasitoid elimination. Our results reveal coordinated molecular and structural changes in the course of MGH differentiation and parasitoid encapsulation, providing a mechanistic model for a powerful innate immune response.